The Effect of Erythropoietin and Its Derivatives on Ischemic Stroke Therapy: A Comprehensive Review - Ma, Yuanyuan; Zhou, Zhiyuan; Yang, Guo-Yuan; Ding, Jing; Wang, Xin (Frontiers in Pharmacology, 2022)
Numerous studies explored the therapeutic effects of EPO on neurodegenerative diseases. Few studies provided comprehensive and latest knowledge of rhEPO treatment during ischemic stroke. In present review, we introduced the structure, expression, function of rhEPO and its receptors in the central nervous system. Furthermore, we comprehensively discussed EPO treatment in pre-clinical studies, clinical trials, and its therapeutic mechanisms including suppressing inflammation. Lastly, advanced studies of the therapy of EPO derivatives in ischemic stroke are also discussed. We wish to provide valuable information on EPO and EPO derivatives treatment in ischemic stroke for basic researchers and clinicians to accelerate the process of their clinical applications.